Lipid binding by the N-terminal motif mediates plasma membrane localization of Bordetella effector protein BteA - Malcova, Ivana; Bumba, Ladislav; Uljanic, Filip; Kuzmenko, Darya; Nedomova, Jana; Kamanova, Jana (The Journal of biological chemistry, 2021)
The respiratory pathogens Bordetella pertussis and Bordetella bronchiseptica employ a type III secretion system (T3SS) to inject a 69-kDa BteA effector protein into host cells. This effector is known to contain two functional domains, including an N-terminal lipid raft targeting (LRT) domain and a cytotoxic C-terminal domain that induces nonapoptotic and caspase-1-independent host cell death. However, the exact molecular mechanisms underlying the interaction of BteA with plasma membrane (PM) as well as its cytotoxic activity in the course of Bordetella infections remain poorly understood. Using a protein-lipid overlay assay and surface plasmon resonance, we show here that the recombinant LRT domain binds negatively charged membrane phospholipids. Specifically, we determined that the dissociation constants of the LRT domain-binding liposomes containing phosphatidylinositol 4,5-bisphosphate, phosphatidic acid, and phosphatidylserine were ∼450 nM, ∼490 nM, and ∼1.2 μM, respectively. Both phosphatidylserine and phosphatidylinositol 4,5-bisphosphate were required to target the LRT domain and/or full-length BteA to the PM of yeast cells. The membrane association further involved electrostatic and hydrophobic interactions of LRT and depended on a leucine residue in the L1 loop between the first two helices of the four-helix bundle. Importantly, charge-reversal substitutions within the L1 region disrupted PM localization of the BteA effector without hampering its cytotoxic activity during B. bronchiseptica infection of HeLa cells. The LRT-mediated targeting of BteA to the cytosolic leaflet of the PM of host cells is, therefore, dispensable for effector cytotoxicity.
Keywords: membránové mikrodomény; buněčná membrána; protein motif; Lipid Bilayers; Humans; HeLa buňky; Protein Binding; Bordetella bronchiseptica; membrane localization domain; lidé; proteinové domény; Bordetella pertussis; lipid–protein interaction; type III secretion system; bakteriální proteiny; plasma membrane; BteA effector protein; lipidové dvojvrstvy; HeLa Cells; surface plasmon resonance; Phospholipids; vazba proteinů; Protein Domains; virulence factor; Saccharomyces cerevisiae; Bacterial Proteins; fosfolipidy; Cell Membrane; Membrane Microdomains